The Effects of Cooperative, Collaborative, and Peer-Tutoring Strategies on English Learners’ Reading and Speaking Proficiencies in an English-Medium Context: A Research Synthesis - Shifang Tang (SAGE Publishing, 2021)
We conducted a research synthesis to examine the impact of cooperative, collaborative, and peer-tutoring strategies on elementary English learners’ (EL) reading and oral proficiencies in studies from the United States. Seven studies were included in the analysis and fully examined regarding the characteristics of sample, intervention, design, and outcome. Effect sizes were reported by the outcome. We found that cooperative/collaborative/peer-tutoring (CCP) strategies boost elementary ELs’ reading comprehension, reading fluency, and phonemic awareness. Ongoing professional development (PD) and coaching help teachers to improve the quality of strategy implementation. The findings indicated that the quality of implementation, the actual amount of time of these strategies are used in the classroom, and the instructional impact of CCP strategies utilization to improve ELs’ English reading and speaking should be the focus of future research.